Fabrication and characterization of photojunction field-effect transistor - Kumar Y.; Kumar H.; Rawat G.; Kumar C.; Goel V.; Pal B.N.; Jit S. (My University, 2025)
In this article, ZnO Quantum Dot (QD)-based photojunction field-effect transistor (photo-JFET) has been fabricated for the detection of ultraviolet (UV) spectrum. The effects of photojunction between the ZnO Quantum Dots (QDs) and deep work function transparent MoO2 is analyzed under the illumination of UV. The illuminated optical power density acts as a floating gate for the JFET. The device was fabricated on a glass substrate using interdigitated electrodes (Ag) followed by ZnO QDs layer and MoO2. The dark current between source and drain was found minimum, 2.79 µA/cm2, in the case of photojunction as compared to the metal semiconductor metal (MSM)ZnO QDs photoconductor 19.32 µA/cm2 at an applied bias of 10 V. The reduction in dark current is attributed due to the effect of the junction formed between ZnO QDs and MoO2 with the rectification ratio of ~347. The MoO2 depletes the ZnO QDs channel between the electrodes and reduces the dark current which in turn helps to improved photodetector characteristics. © Springer Nature Singapore Pte Ltd. 2019.